Private Activity in Telecommunications Remained Stable in 2006 - World Bank (Washington, DC, 2012)
This note states that in 2006 investment commitments to telecommunications projects with private participation remained around the peak level reached in the previous year, according to just-released data from the Private Participation in Infrastructure Project Database. It stresses that as in previous years, stand-alone mobile and multi-service operators accounted for most of the investment and new projects in telecommunications. The concentration of activity in these segments was observed across developing region